A New Species of Physalaemus from Central Brazil (Anura: Leptodactylidae) - Brasileiro, Cinthia A.; Haddad, Celio F. B. [UNESP] (Herpetologists League, 2015)
We describe a new species of Physalaemus from central Brazil. It is characterized by the following combination of traits: medium-sized; snout subelliptical in dorsal view, varying between rounded and protruding in lateral view; head longer than wide; snout long; dorsolateral fold present; small inguinal gland associated with dark ocellus present; tarsal tubercle present; poorly developed tarsal fold present and supernumerary tubercles on feet absent. The advertisement call is a single note with eight harmonics lasting 0.7-1.0 s in duration and emitted at intervals of 0.6-5.8 s. The dominant frequency varies from 1.9 to 3.1 kHz. The occurrence of the new species is in open habitats (disturbed or preserved) in central Brazil.
Keywords: Advertisement call; Amphibia; Cerrado; Leiuperinae; South America; Taxonomy